FedBRICK: Structural Bias Aware Heterogeneous Foundation Model Federated Tuning - Zhang, Yuhang; Wang, Xianda; Sun, Wei; Chen, Jiaxuan; Wang, Fangxin (Proceedings of the AAAI Conference on Artificial Intelligence, 2026)
Model-heterogeneous federated tuning (MHFT) enables the privacy-preserving fine-tuning of foundation models in heterogeneous systems by allowing clients and the server to adopt different model architectures. Depth partial training—where each client updates only a subset of the model's layers—alleviates system heterogeneity but exacerbates client drift, which stems from clients optimizing different objectives and therefore degrades overall performance. Beyond the well-known statistical bias—where non-IID data leads to client drift—we identify a structural bias arising from clients deploying only partial layers of the global model, which serves as an important cause of drift. We further provide a theoretical analysis showing that the possible range of structural bias expands linearly with the number of missing layers. To counter this effect, we introduce FedBRICK (Federated Bias Recovery via Inserted Calibrative Kernels), which inserts tiny BRICKs into each client’s subnetwork. We employ a dual-end layer-wise distillation scheme to train these blocks using both client-side local data and a small public proxy set on the server. This design effectively mitigates the structural bias caused by layer dropping, reduces client drift, and remains practical for storage-constrained devices. Extensive experiments on federated learning benchmarks confirm that FedBRICK delivers up to a 5% average accuracy gain while requiring no more than 1.44% extra storage per client.